2017
DOI: 10.1021/acscatal.7b02418
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced External Oxidant-Free Oxidative Phosphonylation of C(sp2)–H Bonds

Abstract: Considering the synthetic value of phosphonates, developing powerful catalytic methods for the phosphonylation of C­(sp2)–H bonds is important. Herein, we achieve a visible-light-induced external oxidant-free oxidative phosphonylation of C­(sp2)–H bonds via the combination of photocatalysis and proton-reduction catalysis. Mechanistic studies indicate that the visible-light-induced electron-rich arene radical cation is the key reactive intermediate. The synthetic application of this approach is demonstrated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…This dual catalytic CDC approach was subsequently applied to the coupling of azoles ( 78 ) and alcohols ( 97 ) with alkenes ( 128 , Scheme , A)[54b] and for the etherification of arenes. [54c] The same catalytic system enables an oxidant‐free arylation of NH‐sulfoximines ( 131 , Scheme , B).…”
Section: Carbon–heteroatom Bond Formation By Combining Photo‐ and mentioning
confidence: 99%
See 3 more Smart Citations
“…This dual catalytic CDC approach was subsequently applied to the coupling of azoles ( 78 ) and alcohols ( 97 ) with alkenes ( 128 , Scheme , A)[54b] and for the etherification of arenes. [54c] The same catalytic system enables an oxidant‐free arylation of NH‐sulfoximines ( 131 , Scheme , B).…”
Section: Carbon–heteroatom Bond Formation By Combining Photo‐ and mentioning
confidence: 99%
“…This dual catalytic CDC approach was subsequently applied to the coupling of azoles ( 78 ) and alcohols ( 97 ) with alkenes ( 128 , Scheme , A)[54b] and for the etherification of arenes. [54c] The same catalytic system enables an oxidant‐free arylation of NH‐sulfoximines ( 131 , Scheme , B). [54d] Stern–Volmer studies showed that both starting materials quench PC* and generation of both radical cations might be responsible for the C–N coupling.…”
Section: Carbon–heteroatom Bond Formation By Combining Photo‐ and mentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Deactivation can be avoided by either adding the phosphorus reagent slowly to the reaction mixture (Scheme 1a) [3] or employing a-hydroxyalkylphosphonate as am asked, slow-releasing phosphonating reactant (Scheme 1b,c). [6] Despite these significant advances, [7] the reported methods (Scheme 1a-d) require stoichiometric amounts of silver salts as oxidants and are inefficient in converting diarylphosphine oxides into triarylphosphine oxides,w hich are precursors to triarylphosphine ligands. [6] Despite these significant advances, [7] the reported methods (Scheme 1a-d) require stoichiometric amounts of silver salts as oxidants and are inefficient in converting diarylphosphine oxides into triarylphosphine oxides,w hich are precursors to triarylphosphine ligands.…”
mentioning
confidence: 99%